PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA SUB SEKTOR PAKAN TERNAK TAHUN 2010 – 2015 - Adi Suroso, Jimmi Asman, Titin Ruliana (EKONOMIA, 2016)
Companies want to make stock investments aimed at obtaining venture capital to be used for company operations. The company always strives to maximize the value of their shares so that many investors are keen to invest in companies with a way can be measured by its share price.The pricing of the stock one of which is based on the company's performance and can be seen from the financial statements that shows information on the state of a company that can be used as a source of information for decision making.The purpose of this study was to determine the level of liquidity and profitability of the companies sub-sector in the Indonesia Stock Exchange (BEI) together have an effect on stock price period 2010-2015.